GAMBARAN FUNGSI KOGNITIF PADA PASIEN STROKE NON HEMORAGIK MENGGUNAKAN MINI-MENTAL STATE EXAMINATION (MMSE) DI INSTALASI REHABILITASI MEDIK BLU RSUP PROF. DR. R. D KANDOU MANADO - Sinaga, Marchta; Sengkey, Lidwina; Angliadi, Engeliene (e-CliniC, 2014)
Abstract: stroke is a great health concern because it causes pain, disability, mortality and is expensive in cost. Impaired cognitive function is the inability of decision making, impaired memory, disorientation, perceptual disturbances and thinking difficulties. Objective : to examine cognitive functions of non haemorrhagic stroke patients using the Mini-Mental State Examination in the Medical Rehabilitation Department of RSUP Prof. Dr. R. D Kandou Manado. Methods : This study use a cross section descriptive approach (cross sectional). Subjects were non haemorrhagic stroke patients who come to the medical rehabilitation department of Prof.Dr.R.D Kandou from November to December 2013. Results: 20 people (40%) were found with normal cognitive function, 28 people (56%) had mild cognitive impairment, while the remaining 2 people (4%) had severe cognitive impairment. Conclusion: it is found that there are impaired cognitive functions ranging from mild to severe in non haemorrhagic stroke patients, in which could affect the patients survival. Keywords: Stroke, Cognitive Function Abstrak: Stroke merupakan masalah penting bagi kesehatan karena menimbulkan kesakitan, kecacatan, kematian dan memerlukan biaya yang tinggi. Gangguan fungsi kognitif menunjukkan ketidakmampuan mengambil keputusan, gangguan memori , disorientasi, gangguan persepsi dan kesulitan berpikir. Tujuan: Mengetahui gambaran fungsi kognitif pada pasien stroke non hemoragik menggunakan Mini-Mental State Examination (MMSE) di Instalasi Rehabilitasi Medik BLU RSUP Prof. Dr. R. D Kandou Manado. Metode: Penelitian ini bersifat deskriptif dengan pendekatan potongan lintang (cross sectional). Subjek penelitian adalah penderita stroke non hemoragik yang datang ke Instalasi Rehabilitasi Medik BLU RSUP Prof. Dr. R.D Kandou Manado dari November-Desember 2013. Hasil: Ditemukan fungsi kognitif normal 20 orang (40%), gangguan fungsi kognitif ringan 28 orang (56%) dan yang mengalami gangguan fungsi kognitif berat 2 orang (4%). Simpulan: Ditemukan adanya gangguan fungsi kognitif ringan-berat pada pasien stroke non hemoragik yang berpengaruh pada kelangsungan hidup penderita. Kata Kunci: Stroke, Fungsi Kognitif